The use of isodose levels to interpret radiation induced lung injury: a quantitative analysis of computed tomography changes - Knoll, Miriam A.; Salvatore, Mary; Sheu, Ren Dih; Knoll, Abraham D.; Kerns, Sarah L.; Lo, Yeh-Chi; Rosenzweig, Kenneth E. (Quantitative Imaging in Medicine and Surgery; Vol 6, No 1 (February 28, 2016): Quantitative Imaging in Medicine and Surgery (Clinical and Technical Advances on Lung Imaging), 2016)
Background: Patients treated with stereotactic body radiation therapy (SBRT) for lung cancer are often found to have radiation-induced lung injury (RILI) surrounding the treated tumor. We investigated whether treatment isodose levels could predict RILI. Methods: Thirty-seven lung lesions in 32 patients were treated with SBRT and received post-treatment follow up (FU) computed tomography (CT). Each CT was fused with the original simulation CT and treatment isodose levels were overlaid. The RILI surrounding the treated lesion was contoured. The RILI extension index [fibrosis extension index (FEI)] was defined as the volume of RILI extending outside a given isodose level relative to the total volume of RILI and was expressed as a percentage. Results: Univariate analysis revealed that the planning target volume (PTV) was positively correlated with RILI volume at FU: correlation coefficient (CC) =0.628 and P